The relationship between habitat factors and aquatic macrophyte assemblages in the Danube River in Serbia - Vukov, Dragana; Ilić, Miloš; Ćuk, Mirjana; Igić, Ružica; Janauer, Georg A (Archives of Biological Sciences, 2017)
Our objectives were to offer insight into the characteristics of the physical environment in the River Danube in Serbia; and to show the relationship between selected environmental factors and the composition and abundance of macrophyte species. The macrophyte survey method followed the European Standard EN 14184, applying Kohler’s five-level descriptive scale. Principal component analysis was carried out to examine the variation in aquatic vegetation, and to analyze the effect of environmental variables on the aquatic vegetation, redundancy analysis was used. To build a simpler model with fewer explanatory variables, yet sufficiently explaining species variability, forward selection of environmental variables was done. Our results confirmed that physical environmental factors significantly influence the establishment and structure of macrophyte vegetation, with the level of hydrological connectivity to the main river channel being the most important, followed by the transparency of the water column, sediment texture and water-flow velocity. In order to inspect the individual relation between best-fitted plant species and each of selected environmental variables, Spearman’s rank correlation coefficients were calculated. We have distinguished plant species with preferences to specific combinations of analyzed factors. Our results provide a background for future, more specific studies on the macrophyte/habitat relationship. https://doi.org/10.2298/ABS160516116V Received: May 16, 2016; Accepted: June 21, 2016; Published online: October 31, 2016 How to cite: Vukov D, Ilić M, Ćuk M, Igić R, Janauer GA. The relationship between habitat factors and aquatic macrophyte assemblages in the Danube river in Serbia. Arch Biol Sci. 2017;69(3):427-37.